Reciprocity or backfiring? Examining the influence of realistic job previews on applicants' willingness to self‐disclose and use image protection tactics - Wilhelmy, Annika; Truxillo, Donald M.; Funk, Friederike (International journal of selection and assessment, 2022)
Can employers use realistic job previews to encourage applicants to open up in job interviews? We draw on theories of self‐disclosure to examine the association between realistic job previews and applicants' willingness to self‐disclose and use image protection tactics. We also examine perceived competition for the job and Honesty‐Humility as moderators. Results of a between‐subjects 2 × 2 experimental study (N = 396) show that realistic job previews were associated with decreased willingness in applicants to self‐disclose during the interview. This effect was stronger when applicants perceived high competition for the job. Organizational attractiveness and trust toward the employer mediated the effect. There were no direct effects of realistic job previews on image protection tactics. Furthermore, willingness to self‐disclose and use image protection tactics was influenced by applicants' Honesty‐Humility, but Honesty‐Humility did not moderate the relation between job preview condition and willingness to self‐disclose and use image protection tactics. Key points Realistic job previews refer to providing applicants with positive and negative job‐related information. We conducted an online experiment to examine whether realistic job previews help or hinder applicants to open up during a job interview. Realistic job previews may decrease willingness in applicants to open up during the interview, especially when applicants perceive high competition for the job.